A Comprehensive Study on the 2012 Dengue Fever Outbreak in Kolkata, India. (7th August 2013) - Bandyopadhyay, Bhaswati; Bhattacharyya, Indrani; Adhikary, Srima; Konar, Jayshree; Dawar, Nidhi; Sarkar, Jayeeta; Mondal, Saiantani; Singh Chauhan, Mayank; Bhattacharya, Nemai; Chakravarty, Anita; Biswas, Asit; Saha, Bibhuti
Abstract : Background . Dengue viruses (DV) belong to the family Flaviviridae, with four serotypes referred to as DV-1, DV-2, DV-3, and DV-4. A large-scale outbreak of dengue fever occurred in 2012 involving several districts of West Bengal. Objective . To present a comprehensive picture of the dengue fever outbreak in 2012 and to identify the prevailing serotypes. Materials and Methods . Serum samples were collected from suspected dengue fever cases. Samples from fever cases <5 days duration were tested for dengue NS1 antigen employing Pan Bio (Australia) NS1 ELISA kit. Serum samples of ≥5 days fever were tested for dengue-specific IgM by MAC ELISA test kit prepared by the National Institute of Virology Pune, India. Serotyping of dengue samples was done by dengue-specific reverse transcriptase polymerase chain reaction (RT-PCR). Results . The number of dengue cases in 2012 clearly outnumbered the dengue cases in 2010 and 2011. The majority of the cases were in the age group 11–30 years with a male preponderance. Outbreak occurred during the months of Aug.–Nov. indicating increased vector transmission in the monsoon and postmonsoon periods. The prevailing serotypes in this outbreak were Den1, Den3, and Den4.